Breve storia della democrazia Da Atene al populismo - Marchettoni, Leonardo (Manuali - Scienze Sociali, 2018)
The purpose of this volume is to retrace the history of democratic institutions, from their classical beginning in Athens in the 5th century BC, to the bourgeois revolutions; from the success of representative democracy to the affirmation of constitutional democracies in the 20th century and, finally, from the contemporary crisis to the rise of populist parties. This book aims at offering an overall picture which, while summarising a general overview, combines the history of institutions with the history of political thought, in the belief that such a point of view allows a better understanding of the dynamics underlying the sequence of events.